Analyzing Perceived Causes of Business Failure: A Factor Analytic Approach (PYC Nepal Journal of Management, 2010)
This paper is originally presented at the “International Seminar on Management” on “Enhancing Enterprise Effectiveness for Global Challenges” organised by Brihaspati College, Siddharthnagar on 3rd and 4th April 2010. The author acknowledges that the printed version of the paper has come after the suggestions from the Editorial Committee.This paper analyzes respondents view through a questionnaire survey on the perceived causes of business failure in the context of Nepal. From the results of the survey conducted, it is observed that the most serious problem of sickness in firms can be condensed into three main categories, viz., managerial, financial and economic. The study thus provides support for the causes of firms’ sickness that can be categorized into three fundamental problems: Inaccessibility to debt, the lack of knowledge of the owner/manager, and the business climate. The sick firms have found these three problems most impelling for their failure.